An analysis of outcomes and predictors of intensive care unit bouncebacks in a mature trauma system. Issue 4 (April 2020) - Bradburn, Eric H.; Jammula, Shreya; Horst, Michael A.; Morgan, Madison; Vernon, Tawnya M.; Gross, Brian W.; Miller, Jo Ann; Cook, Alan D.; Kim, Patrick K.; Von Nieda, Danielle; Rogers, Frederick B.
Abstract : BACKGROUND: With the recent birth of the Pennsylvania TQIP Collaborative, statewide data identified unplanned admissions to the intensive care unit (ICU) as an overarching issue plaguing the state trauma community. To better understand the impact of this unique population, we sought to determine the effect of unplanned ICU admission/readmission on mortality to identify potential predictors of this population. We hypothesized that ICU bounceback (ICUBB) patients would experience increased mortality compared with non-ICUBB controls and would likely be associated with specific patterns of complications. METHODS: The Pennsylvania Trauma Outcome Study database was retrospectively queried from 2012 to 2015 for all ICU admissions. Unadjusted mortality rates were compared between ICUBB and non-ICUBB counterparts. Multilevel mixed-effects logistic regression models assessed the adjusted impact of ICUBB on mortality and the adjusted predictive impact of 8 complications on ICUBB. RESULTS: A total of 58, 013 ICU admissions were identified from 2012 to 2015. From these, 53, 715 survived their ICU index admission. The ICUBB rate was determined to be 3.82% (2, 054/53, 715). Compared with the non-ICUBB population, ICUBB patients had a significantly higher mortality rate (12% vs. 8%; p < 0.001). In adjusted analysis, ICUBB was associated with a 70% increased odds ratio for mortality (adjusted odds ratio, 1.70; 95% confidence interval, 1.44–2.00; p < 0.001). Adjusted analysis of predictive variables revealed unplanned intubation, sepsis, and pulmonary embolism as the strongest predictors of ICUBB. CONCLUSION: Intensive care unit bouncebacks are associated with worse outcomes and are disproportionately burdened by respiratory complications. These findings emphasize the importance of the TQIP Collaborative in identifying statewide issues in need of performance improvement within mature trauma systems. LEVEL OF EVIDENCE: Epidemiological study, level III.